Local Wisdom to Overcome Covid-19 Pandemic of Urug and Cipatat Kolot Societies in Bogor, West Java, Indonesia - Bahagia Bahagia; Bambang Hudayana; Rimun Wibowo; Zuzy Anna (Forum Geografi, 2020)
Local wisdom can be interpreted as principles of life, behaviour, rules, and punishments, as well as a view of life that regulate life, so that it can regulate and managing natural resources in the natural, social, and economic environments. Even local knowledge have adapted to environment obstacle. This research aims to investigate traditionally local knowledge for confronting Covid-19 pandemic. The method used is qualitative with an ethnography approach and literature review. Data are collected through in-depth interviews with leaders of Urug and Cipatat Kolot societies. In order to investigate Baduy and Ciptagelar communities used a literature review. Data are supported by documentation and observation sources. The sample is selected using a purposive sampling technique. The result is analysed through triangulation, which is by mixing some gathered data methods. The result is that Urug society allocates rice each year from their paddy yields to the vulnerable groups such as orphans, elderlies, widows, and persons need most. Secondly, collective action is used to jump the capacity of people like women through nujuh bulanan. Thirdly, societies exert taboo to combat disaster and Covid-19, including by prohibiting community from trading paddies and rice. Another finding is that indigenous knowledge uses some life strategies and utilizes natural capital optimally for overcoming life perturbances. The last finding is that local knowledge has preserved agriculture jobs as a venue to survive.